Desarrollo de un sistema para el control de vendedores utilizando geolocalización con aplicaciones móviles. Caso de estudio: DeviesCorp S.A. - Alvarez Velasco, Erika Cecibel (2020)
The present work is to develop a system that allows control of the sellers of the company DeviesCorp S.A., in order to guarantee its effectiveness. The system allows you to verify that sellers are on their routes, looking for new customers interested in the products that the company sells, and making the respective visits to them. To carry out this work, we used the SCRUM methodology, which is an agile development model, which focuses on the exchange, communication and decreasing intermediate components. This has a great capacity to respond to changes, which are not understood as a problem but as something necessary for the product to be better and meet customer requirements. Through bibliographic research, the tool and programming language that allow them to have an optimal system performance, it is of great importance to carry out an analysis of the requirements of the mobile application to achieve the implementation of the system, which this allows the integrity of the data. During the development of the system we use current technological tools such as the Android Studio operating system, MySQL, PHP, HTML to design the structure of the application and its respective database that allow the development of mobile applications, in addition to others such as geolocation, technology that use data obtained from an individual computer or mobile device to identify or describe its actual physical location. We carried out test to verify that the mobile application works correctly as data entry and modification.